Characterization and expression profile of CaNAC2 pepper gene - Guo, Wei-Li; Wang, Shu-Bin; Chen, Ru-Gang; Chen, Bi-Hua; Du, Xiao-Hua; Yin, Yan-Xu; Gong, Zhen-Hui; Zhang, Yu-Yuan (Frontiers in Plant Science, 2015)
The plant-speciﬁc NAC (NAM, ATAF, and CUC) transcription factors have diverse role in development and stress regulation. A new transcript encoding NAC protein, homologous to nam-like protein 4 from Petunia was identiﬁed from an ABA-regulated subtractive cDNA library of Capsicum annuum seedling. Here, this homolog (named CaNAC2) from Capsicum annuum was characterized and investigated its role in abiotic stress tolerance. Our results indicated that a plant-speciﬁc and conserved NAC domain was located in the N-terminus domain of CaNAC2 which was predicted to encode a polypeptide of 410 amino acids. Phylogenetic analysis showed that CaNAC2 belonged to the NAC2 subgroup of the orthologous group 4d. The protein CaNAC2 was subcellularly localized in the nucleus and it had transcriptional activity in yeast cell. CaNAC2 was expressed mainly in seed and root. The transcription expression of CaNAC2 was strongly induced by cold, salt and ABA treatment and inhibited by osmotic stress and SA treatment. Silence of CaNAC2 in virus-induced gene silenced pepper seedlings resulted in the increased susceptibility to cold stress and delayed the salt-induced leaf chlorophyll degradation. These results indicated that this novel CaNAC2 gene might be involved in pepper response to abiotic stress tolerance.